Oniomania dan Literasi Keuangan Milenial : Kajian Sistematis atas Perilaku Konsumsi Digital - Dhiptya Ratri Anggraheni (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital transformation is reshaping the way today’s consumers manage their finances, encouraging spending patterns that mirror compulsive buying behaviour oniomania. This study therefore examines how financial literacy influences such compulsive consumption in the context of an increasingly technology‑driven era. Guided by the PICOC framework, this review systematically analyzed six relevant academic articles using a Systematic Literature Review (SLR) approach. Findings indicated that a combination of psychosocial factors such as stress along with a need for social validation, coupled with incentivized digital engagement like tailored ads, online shopping deals, and BNPL payment options contributed to oniomania. Additionally, the components of financial literacy such as knowledge, attitudes towards finance and budgeting skills contributed positively by reducing the likelihood to engage in compulsive consumption. These findings underscored the need for immediate action towards policy change focusing on providing integrated tech-based financial education and developing more responsible digitized financial tools. The review lays down useful concepts for programmatic strategies directed at legislation meant to nurture healthier and sustainability-oriented regimes of digital consumption.